GEOPHYSICAL CHARACTERIZATION OF BASEMENT ROCK FOR GROUNDWATER AND MINERALIZATION POTENTIAL USING VERY LOW FREQUENCY – ELECTROMAGNETIC (VLF-EM) TECHNIQUES AT SITE “G” AROUND IBADAN METROPOLIS, SOUTHWESTERN BASEMENT COMPLEX, NIGERIA - Ibrahim Abdulbariu; Hassan Jubril Izge; Mu’awiya Baba Aminu; Jamal Osumanu; Habeeb Ayoola Ayinla; David Appiah; Ibrahim O. Ibrahim (Geological Behavior)
The research area, site “G” is located in the city of Ibadan and is surrounded by the basement complex rock mainly migmatite-gneiss and been a hard rock, it is not alienated from the problem of water scarcity. In this region, water is usually encountered either in weathered zone or fractured basement which serve as a conduit for groundwater passage. It is also along this fracture that materials such as quartzo-feldsparthic minerals occur and tend to heal the fracture, hence the need for intensive geological and geophysical exploration to locate this important basement fracture. Very low frequency Electromagnetic (VLF-EM) alongside with geological survey was adopted and conductivity data were acquired along fifteen VLF traverses utilizing very low frequency of about 15 KHz using ABEM WADI survey equipment. 13 profiles were in the east-west (E-W) direction which is the dip direction of the structural elements, while the 2 profiles were in north-south (N-S) direction to serve as a control. The acquired data were analyzed, filtered and displayed inform of profiles and Karous-Hjelt (K-H) filtered pseudo-section to show conductivity and resistivity in 2-D. The results reveal pocket of conductive zones which have been considered as fractures with different dimension and orientation. Most are single fractures, while some are closely spaced double fractures, some of which are connected to each other in depth. Also, some of these fractures contain water while some are dry, some are even suspected to be healed with quartzo-feldsparthic minerals and all of these depend on the conductivity / resistivity signature exhibited by the fractures. Therefore, it can be concluded that VLF has effectively characterise the basement into fractures that contain water, barren fracture and even fracture that contain quartzo-feldsparthic vein.